Analysis of Bio-Sorption of Cr(VI) onto Raw Rice Husk by a Hybrid Theoretical Model Using Results of Batch Experiments - Debasish Sarkar; Sudip K Das; Amitava Bandyopadhyay (Adsorption Science & Technology)
In this study, batch adsorption experiments are conducted for removing Cr(VI) from its aqueous solution using raw rice husk after its characterization by scanning electron microscopy, BET and Fourier transform infrared spectroscopy analyses. The effects of different operating parameters are investigated and optimized. The maximum percentage of removal observed was 99% under optimal operating conditions. Experimental results follow the Langmuir adsorption isotherm reasonably well. A hybrid mathematical model that takes into account the shrinking core approach coupled with the well-known progressive conversion model has been proposed to simulate the dynamic behaviour of the present system using the results obtained from the batch adsorption experiments. The proposed model can also be potentially applicable to any similar other solid–liquid adsorption–diffusion system. Based on the experimental findings and theoretical analyses carried out in this study, several recommendations are holistically put forward for developing the understanding of the adsorptive removal of heavy metals including Cr(VI) and other pollutants.